When trust is not enough: Bank resolution, SPE, Ring-fencing and group support - Mathias Dewatripont; Marie Montigny; Grégory Nguyen (National Bank of Belgium, 2021)
This discussion paper investigates the differences existing between the Single Point of Entry and the Multiple Point of Entry resolution models and links this question to the issue of support that bank subsidiaries can expect from their parent companies both in resolution and in normal insolvency proceedings. Given that parental support remains imperfect in these two resolution models, the paper concludes that existing safeguards aiming at preserving the corporate interests of subsidiaries remain needed and justified. The paper then identifies potential avenues that could be further explored to reinforce the support model and thereby reduce incentives to adopt ring-fencing measures.
Keywords: G10; G21; G28; K22; 330; Bank resolution; SPE; Banking crisis; bail-in; bankruptcy